MOTIVASI INDONESIA MENGAKUISISI LADANG MINYAK DI ALJAZAIR PADA TAHUN 2013 - Ahmadi "; Faisyal Rani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study describes the acquisition of Indonesia to the oil fields in Algiers in 2013. Themain factor is the motivation to acquire oilfields Indonesia is Indonesia's economic and politicalinterests.The data was obtained from books, and from the internet. This research analyzed byusing the theory of decision making.This study explains that Indonesian policy acquired oil fields in Algeria to meet the needsof the oil in Indonesia. the existence of good relations between Indinesia and Algiers, and thechallenges of oil exploration in Indonesia.Keyword: acquisition, motivation, national interest.